FBMC vs. PAM and DMT for High-Speed Wireline Communication - Jeremy Cosson-Martin; Jhoan Salinas; Hossein Shakiba; Ali Sheikholeslami (IEEE Open Journal of Circuits and Systems)
This paper demonstrates the first silicon-verified FBMC encoder and decoder designed to emulate beyond $224Gb/s$ wireline communication. It also compares the performance of FBMC to PAM and DMT in three steps. First, the digital power and area consumption are compared using measured results from the manufactured test chip. Second, the data rate is determined using lab-measured results. And third, the performance when subject to notched channels is analyzed using simulation results. Finally, we present a method to emulate wireline links while reducing the emulator complexity and simulation time by one to two orders of magnitude over conventional over-sampled techniques. Our analysis indicates that given a smooth channel and an SNR which enables an average spectral efficiency of $4bits/sec/Hz$ at a bit-error rate of 10-3, both DMT and FBMC perform similarly to a conventional PAM-4 link. However, when noise is reduced and a spectral notch is applied, thereby achieving an average spectral efficiency of $4.6bits/sec/Hz$ , DMT and FBMC can outperform PAM by 2.1 and 2.3 times, respectively. In addition, we estimate FBMC’s encoder and decoder power consumption at $1.53pJ/b$ and $1.98pJ/b$ , respectively, and area requirement at $0.07mm^{2}$ and $0.17mm^{2}$ , respectively, which is similar to DMT. These values are competitive with similar $22nm$ PAM transceivers, suggesting that DMT and FBMC are viable alternatives to PAM for next-generation high-speed wireline applications.